2011
DOI: 10.12693/aphyspola.120.153
|View full text |Cite
|
Sign up to set email alerts
|

RBS/Channeling and TEM Study of Damage Buildup in Ion Bombarded GaN

Abstract: A systematic study on structural defect buildup in 320 keV Ar-ion bombarded GaN epitaxial layers has been reported, by varying ion fluences ranged from 5 × 10 12 to 1 × 10 17 at./cm 2. 1 µm thick GaN epitaxial layers were grown on sapphire substrates using the metal-organic vapor phase epitaxy technique. Rutherford backscattering/channeling with 1.7 MeV 4 He beam was applied for analysis. As a complementary method high resolution transmission electron microscopy has been used. The later has revealed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…42 −44 In fact, it was suggested that strain induced by implantation defects is the driving force behind the defect mobility and dynamic annealing in GaN, leading to the change of defect microstructure as the fluence increases. 45 Detailed XRD studies on GaN NWs and NW heterostructures showed that, due to their vertical alignment, NWs can be studied by laboratory XRD in a similar way as planar heterostructures. 46,47 However, the diffraction intensity is strongly reduced due to the reduced sample volume and the fact that, due to the relatively high tilt between NWs, only a fraction of them will be well-oriented to satisfy the Bragg condition and contribute to the Bragg peak intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 −44 In fact, it was suggested that strain induced by implantation defects is the driving force behind the defect mobility and dynamic annealing in GaN, leading to the change of defect microstructure as the fluence increases. 45 Detailed XRD studies on GaN NWs and NW heterostructures showed that, due to their vertical alignment, NWs can be studied by laboratory XRD in a similar way as planar heterostructures. 46,47 However, the diffraction intensity is strongly reduced due to the reduced sample volume and the fact that, due to the relatively high tilt between NWs, only a fraction of them will be well-oriented to satisfy the Bragg condition and contribute to the Bragg peak intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have reported similar strain formation in GaN for different implantation conditions 42,43,44 . In fact, it was suggested that strain induced by implantation defects is the driving force behind the defect mobility and dynamic annealing in GaN leading to the change of defect microstructure as the fluence increases 45 . Detailed XRD studies on GaN NWs and NW heterostructures showed that, due to their vertical alignment, NWs can be studied by laboratory XRD in a similar way as planar heterostructures 46 , 47 .…”
Section: Strain and Morphologymentioning
confidence: 99%
“…The damage profiles exhibit both a pronounced peak typical for direct backscattering from point defect clusters arising in the implanted zone and strong artificial backscattering tails for the deeper, unimplanted regions of the sample suggesting the formation of stacking faults and dislocation loops. Indeed, for the case of room temperature implantation into GaN the strongly increasing damage level was attributed to both displaced atoms in point defect clusters as well as extended defects (Pagowska et al, 2011). However, in GaN the direct backscattering peak arises at the depth of maximum nuclear energy deposition while for ZnO the maximum of the defect peak also starts in this region but then shifts deeper towards the end of range of the implanted Ar ions.…”
Section: Comparison Of Damage Build-up In Zno and Ganmentioning
confidence: 99%
“…2 the ratio of channeled to random stopping power is constant and amounts to 0.7 in the energy range studied. Results of our recent study of the defect buildup in GaN due to Ar-ion implantation has been published elsewhere [17]. Defect distributions produced by 320 keV Ar-ion bombardment extend over 300 nm and the increase of their concentration follows the three-step accumulation model [18].…”
Section: Mev Incidentmentioning
confidence: 99%